(untitled) (Innovative professional education, 2025)
The article explores the impact of the European Green Deal on the development of vocational education and training across various professional sectors. The study examines the key environmental challenges and opportunities facing the VET system and highlights the necessity of adapting educational programs to align with sustainability goals. The role of education in equipping the workforce with green competencies and knowledge essential for the transition to a sustainable economy is outlined